Affective Mapping - FLATLEY, Jonathan (Harvard University Press, 2009)
The surprising claim of this book is that dwelling on loss is not necessarily depressing. Instead, embracing melancholy can be a road back to contact with others and can lead people to productively remap their relationship to the world around them. Flatley demonstrates that a seemingly disparate set of modernist writers and thinkers showed how aesthetic activity can give us the means to comprehend and change our relation to loss
10.4159/9780674036963
Keywords: American literature / 19th century / History and criticism; American literature / 20th century / History and criticism; Melancholy in literature; Melancholy / Social aspects; Modernism (Literature); Melancholie / Motiv; Moderne; Literatur; LITERARY CRITICISM / Semiotics & Theory